Homicide of children aged 0–4 years, 2003–04: results from the National Violent Death Reporting System. (14th December 2006) - Bennett, M D; Hall, J; Frazier, L; Patel, N; Barker, L; Shaw, K
Abstract : Introduction: To better understand, and ultimately prevent, infant/child homicide, it is imperative to more thoroughly elucidate the circumstances and conditions related to such instances. Data were obtained from the US National Violent Death Reporting System (NVDRS) to illuminate circumstances related to homicide among children aged 4 years or less, and to identify demographic groups which may be at increased risk. Methods: The NVDRS is an active surveillance system that provides comprehensive information on all violent deaths that occur within participating states within the US. Standard statistical tests were conducted to determine homicide rates among children ages 0–4 across states that provided data for both 2003 and 2004 (Alaska, Maryland, Massachusetts, New Jersey, Oregon, South Carolina, and Virginia). These data were further used to investigate infant/child homicides by race, gender, and other relevant circumstances (for example, victim-suspect relationship, weapon type, and location of homicide). A Poisson regression model was fitted to the sample data to investigate the multivariate relationship between the infant/child homicide rate and available demographic information. Results: The 2003 homicide rate for children ages 0–4 was 3.0 per 100 000 population. The 2004 homicide rate was 2.5 per 100 000 population. African Americans were 4.2 times as likely as whites to be victims of homicide. Suspects were commonly parents/caregivers. The vast majority of infant/child homicides occurred in houses or apartments, using weapons that include household objects. Conclusion: Homicides of infants and young children are most often committed in the home, by parents/caregivers, using "weapons of opportunity". This suggests that the risk of infant/child homicide is greatest within the primary care giving environment. Moreover, the use of "weapons of opportunity" may be indicative of maladaptive stress responses. Prevention and intervention strategies to reduce infant/child homicide should target the home environment and attend to maladaptive stress responses.